A note on brain gain and brain drain: Permanent migration and education policy - Alexander Haupt; Tim Krieger; Thomas Lange (Center for Economic Studies and ifo Institute (CESifo), 2010)
In this note, we present a novel channel for a brain gain. Students from a developing country study in a developed host country. A higher permanent migration probability of these students appears to be a brain drain for the developing country in the first place. However, it induces the host country to improve its education quality, as a larger share of the generated benefits accrue in this host country. A higher education quality raises in turn the human capital of the returning students. As long as the permanent migration probability is not too large, this positive effect causes both aggregate and per-capita human capital to increase in the developing country. Thus, a brain gain occurs.
Keywords: F22; I28; J61; O15; 330; brain gain; education policy; human capital; return migration; Brain Drain; Bildungsinvestition; Dienstleistungsqualität; Bildungsniveau; Rückwanderung; Nord-Süd-Beziehungen; Theorie